(untitled) (Annals of Medical Research, 2021)
Aim: The American Joint Committee on Cancer (AJCC) tumor-node-metastasis (TNM) cancer staging system is the strongest prognostic parameter for colorectal cancer. However, additional markers are needed to improve clinical decision making. The aim of this study was to investigate the effects of lenfovascular invasion (LVI), perineural invasion (PNI) and peritumoral lymphocytic reaction (PLR) on lymph node involvement in surgically treated colon cancer patients. Materials and Methods: The historical records of patients having undergone colon cancer surgery in the Department of General Surgery were evaluated. In addition to demographic data and pathological TNM staging, parameters including tumor location, type, differentiation, LVI, PNI, PLR and tumor growth pattern were recorded and analyzed. p<0.05 was considered as statistically significant. Results: The study group of 71 patients consisted of 39 (54.9%) men and 32 (45.1%) women with a mean age of 65.1±12.3 (range: 39- 89) years. Tumors were located in the ascending colon in 18 (25.4%) patients, in the transverse colon in 3 (4.2%), in the descending colon in 8 (11.2%) and in the sigmoid colon in 42 (59.2%) patients. According to the postoperative histopathological examinations LVI was detected in 65 (91.6%) cases whereas PNI was found in 14 (19.7%) cases. PLR was detected in 69 (97.2%) cases that was mild in 53 (74.6%) and moderate in 16 (22.6%) cases. The incidence of PNI was significantly higher in stage N2 cases (p=0.001). On the other hand, no significant differences were found among N stage groups regarding LVI or PLR (p=0.409 and p=0.441, respectively). Although it was detected that LVI and PLR were present concomitantly in 63 (88.7%) cases, no significant differences were detected between mild, moderate or negative PLR with respect to LVI positivity (p=0.748). Conclusion: PNI was associated with increased lymph node involvement. Larger prospective randomized controlled studies are needed to be conducted in order to establish additional prognostic parameters in colon cancer surgery.